2004
DOI: 10.1063/1.1648638
|View full text |Cite
|
Sign up to set email alerts
|

Plume formation in strongly temperature-dependent viscosity fluids over a very hot surface

Abstract: Plume formation in a strongly temperature-dependent viscosity fluid placed on a very hot surface involves an intermediate step-small-scale convection in the thermal boundary layer. We perform numerical simulations and suggest a simple analysis of this process using the stagnant lid convection theory and Canright and Morris' theory of Rayleigh-Taylor instability of two layers with different viscosities. We show that plume formation can approximately be predicted from the requirement that the growth of the large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
0
23
1
Order By: Relevance
“…[10]. The mentioned bibliography shows interest in different phenomena related to the mantle, such as magma [14], plate formation [23], and plumes formation [20,6]. Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10]. The mentioned bibliography shows interest in different phenomena related to the mantle, such as magma [14], plate formation [23], and plumes formation [20,6]. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of dependencies have been taken into account: polynomial dependence is considered in Ref. [9] but the most common is an exponential dependence as the dependence that best explains the behaviour of mantle convection [24,20,6,7,11]. There are some experiments adapting scales to small cells [19,25,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To accurately predict the flow behaviour, it is necessary to take into account this variation of viscosity with temperature. The effects of temperature-dependent viscosity on the boundary layer flow and heat transfer is investigated by many authors such as Jang and Lin (1988), Pop et al (1992), Massoudi and Christie (1995), Kafoussias and Williams, (1995), Hady et al (1996), , , Abel et al (2002), Massoudi and Phuoc (2004), Begai (2004), Ke and Solomatov (2004), Ali (2006), Jayanthi and Kumari (2006), Mahmoud (2007a,b,c), Hayat et al (2007a), Massoudi et al (2008), Hayat and Ali (2008), and Mukhopadhyay and Layek (2008). Gebhart (1962) has shown that the viscous dissipation effect plays an important role in natural convection in various devices processes on large scales (or large planets).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal plumes in deep mantle have been simulated by computational geodynamics (CGD) models with influence of various parameters, such as viscosity, composition and phase changes, which are based on abruptly increased surface temperatures of 200e2000 C (Olson et al, 1987;Ji and Nataf, 1998;Kiefer and Kellogg, 1998;Montague et al, 1998;Goes et al, 2004;Ke and Solomatov, 2004;Davies, 2005). CGD simulations showed the formation of unstable thermal boundary layer up to the evolution of plumes, plume detachment and dissipation of heat in the bulk fluid (see review by Schubert et al (2001) and Davies (2005)) identical to observations of Foster (1969) and Sparrow et al (1970).…”
Section: Introductionmentioning
confidence: 99%